VD_FINDINFO Jug / 2011 / 261 vom 9. November 2011 - VD Tribunal cantonal (2011)
ABUS D'AUTORITÉ, LÉSION CORPORELLE SIMPLE, AGRESSION, NON-LIEU | 123 CP, 134 CP, 312 CP, 318 CPP (CH), 319 CPP (CH), 393 CPP (CH)